The residential leaseholder's interest in construction operations. Issue 2 (8th July 2019) - Sawtell, David R.F.
Abstract : Purpose: The owner of residential long leasehold can be significantly affected by construction operations to the building, whether during its initial construction or its subsequent repair, renovation or improvement. This paper aims to consider how a leaseholder has an interest in such construction operations and the extent to which this is taken into consideration in their procurement. Design/methodology/approach: The paper is a general review of how construction law interfaces with property law interests, rights and obligations in the case of a residential leaseholder. The first part of the paper outlines the issues raised by construction operations. The second part of the paper queries the efficacy of any right of redress the leaseholder might have in respect of construction defects. The third part considers the limited nature of the leaseholder's right to be consulted about construction operations. The paper is predominantly doctrinal in approach, although it references socio-legal research. The paper also contrasts the English law position with Australia. Findings: The paper concludes that leaseholders have limited input into the procurement of construction operations despite their interest in them. Property law can be used to regulate construction law operations. Originality/value: To date, the literature dealing specifically with the position of leaseholders, consultation obligations and construction operations has been limited. This paper brings together property law and construction law in analysing the findings of the Hackitt Report into the Grenfell Tower disaster.